Batch preparation method and application of single crystal boron nitride wafer based on copper-nickel single crystal film
By combining Cu80Ni20(111) single crystal thin film substrate with porous precursor carrier and stacked fault wafer carrier, the problems of inconsistent crystal orientation and uneven surface in the mass production of boron nitride thin films were solved, realizing efficient and uniform preparation of single crystal boron nitride wafers and broadening its application in high-end devices.
Patent Information
- Application Number
- CN202511564973.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-30
- Publication Date
- 2025-11-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing technologies make it difficult to achieve mass production of large-size, single-crystal, atomically flat, and highly uniform boron nitride thin films, resulting in problems such as inconsistent crystal orientation, uneven surface, poor batch repeatability, and insufficient scalability.
A Cu80Ni20(111) single crystal thin film was used as the growth substrate. A stable borazine vapor precursor was formed by combining a porous precursor carrier and a stacked wafer carrier through thermal conversion treatment. The release rate and direction of the vapor precursor were optimized, and epitaxial growth was carried out in a CVD system to ensure gas flow uniformity and thermal field consistency.
It has enabled the batch synchronous fabrication of high-quality single-crystal boron nitride wafers with consistent crystal orientation and ultra-flat surface, improving production efficiency and process repeatability. It is applicable to fields such as two-dimensional material devices, deep ultraviolet optoelectronic devices, quantum devices and integrated circuit packaging.
Smart Images

Figure CN121023635A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for mass production of single-crystal boron nitride wafers based on copper-nickel single-crystal thin films and its application, belonging to the field of two-dimensional material preparation and nanoelectronic device manufacturing technology. Background Technology
[0002] Hexagonal boron nitride (h-BN) is a typical two-dimensional layered material with a honeycomb lattice structure similar to graphene. However, due to its wide bandgap (approximately 5.9 eV), high thermal stability, electrical insulation, atomically flat surface, and excellent dielectric properties, it is widely used in cutting-edge fields such as next-generation nanoelectronic devices, deep ultraviolet optoelectronic devices, two-dimensional material heterostructures, field-effect transistors, quantum devices, and tunneling insulating layers. In two-dimensional material device architectures, h-BN is often used as a substrate, encapsulation layer, or insulating layer, playing a crucial role in reducing interface impurities, suppressing carrier scattering, and improving device reliability.
[0003] As research on two-dimensional materials gradually moves towards practical devices and industrialization, more stringent quality requirements are being placed on h-BN materials, especially for large-size, single-crystal, atomically flat, highly uniform, and grain-bound boron nitride thin films. Therefore, achieving controllable preparation and mass production of single-crystal h-BN wafer-level materials has become a key technological bottleneck that urgently needs to be addressed in this field.
[0004] Currently, the mainstream method for preparing two-dimensional h-BN materials is epitaxial growth technology based on chemical vapor deposition (CVD). While traditional polycrystalline metal foils (such as Cu and Ni) are readily available and inexpensive, their multi-oriented surface grains and unstable growth environment often result in a polycrystalline h-BN film with dense grain boundaries, inconsistent crystal orientations, and a significant decrease in device performance. In recent years, the academic community has begun to explore epitaxial growth using single-crystal metal substrates (such as Cu(111), Ni(111), and Pt(111)), which has significantly improved the crystal orientation consistency and structural integrity of h-BN. In particular, systems based on Cu-Ni alloys have shown great potential in regulating catalytic activity and adsorption behavior. However, even under single-crystal metal substrate conditions, the following challenges still generally exist: 1. Nucleation density of large-area single-crystal h-BN is difficult to control, and dislocation defects and interfacial tension mismatch are prone to occur at grain merging points; 2. The pyrolysis products of the precursor ammonia borane (NH3·BH3) are complex and have poor stability, and are prone to producing impurity byproducts such as oligomeric ammonia borane, which leads to uneven film and introduces impurities. 3. Uneven gas flow field distribution within the growth system and gradient in the supply of source material lead to fluctuations in thickness, uniformity, or crystal orientation among multiple wafers. 4. It is difficult to construct an efficient, repeatable process route suitable for mass production of large-size wafers, which limits the industrial application.
[0005] Most of the single-crystal h-BN preparations reported in the literature are still at the single-wafer level. Even if single-crystal films at the centimeter level can be achieved, they usually rely on finely controlled local airflow conditions and manually controlled temperature distribution, making it difficult to scale up to industrial-scale multi-wafer batch parallel production.
[0006] Furthermore, conventional CVD systems use simple evaporation boats as precursor carriers, lacking effective control over the evaporation rate and direction of the precursor. This easily leads to rapid precursor depletion and unstable local concentrations, affecting film stability and consistency. In terms of wafer loading methods, differences in the thermal field or airflow path of traditional parallel or stacked structures also introduce significant batch variations.
[0007] Therefore, how to construct a single-crystal h-BN wafer growth system suitable for batch, reproducible, and high-crystal-quality preparation by considering multiple dimensions such as stable precursor supply, uniformity of gas transport paths, interfacial coupling strength, and synergistic optimization of system structure and thermal / fluid field is currently a research hotspot and key challenge in this field. This invention is proposed to address this issue. Summary of the Invention
[0008] The purpose of this invention is to provide a method for the simultaneous batch production of high-quality single-crystal boron nitride wafers based on a copper-nickel single-crystal thin film substrate and a gas source / flow field precision control strategy, which solves the problems of inconsistent crystal orientation, uneven surface, poor batch repeatability and insufficient scalability in the current preparation of single-crystal h-BN wafers.
[0009] The method for mass production of single-crystal boron nitride wafers provided by this invention includes the following steps: S1. The ammonia borane precursor is thermally converted to form a stable source system for releasing the borazine gaseous precursor. S2. The precursor processed in step S1 is placed in the precursor receiving tube in a precursor carrier with a porous structure to regulate the release rate and direction of the gaseous precursor. S3. Place the growth substrate in a wafer carrier, place it in the CVD reaction chamber, and introduce a mixture of hydrogen and argon gas. Perform epitaxial growth at 1050-1100°C to achieve the simultaneous preparation of multiple single-crystal boron nitride wafers.
[0010] In this invention, the growth substrate is Cu. 80 Ni 20 (111) Single-crystal thin films; The Cu 80 Ni 20(111) The surface roughness of the single crystal thin film is less than 0.5 nm, which has excellent atomic-level flatness and crystal orientation consistency, promoting the single crystal epitaxy of h-BN.
[0011] Preferably, the Cu 80 Ni 20 (111) Single-crystal thin films are prepared by a method comprising the following steps: A copper-nickel alloy thin film was deposited on a c-plane sapphire substrate by magnetron sputtering and annealed at 1000-1100℃ for 60-180 minutes in a mixed atmosphere of hydrogen and argon to form Cu. 80 Ni 20 (111) Oriented single-crystal thin film substrate.
[0012] In this invention, the Cu 80 Ni 20 (111) The single crystal thin film provides a template for h-BN. Its atomically flat (111) crystal plane provides a lattice-matching template for the growth of h-BN, guiding h-BN atoms to align in a specific direction, thereby growing a large-area single crystal with consistent crystal orientation.
[0013] The Cu 80 Ni 20 (111) Single crystal thin films also have the functions of catalysis and growth regulation. The Cu-Ni alloy composition provides catalytic activity, ensuring that the precursor is effectively decomposed and high-quality h-BN is generated, while suppressing unnecessary side reactions or multilayer growth.
[0014] The Cu 80 Ni 20 (111) Single-crystal thin films can be prepared on insulating c-plane sapphire substrates using standard semiconductor processes (magnetron sputtering, annealing), which makes it easier for the grown h-BN wafers to be transferred or used directly for device manufacturing, avoiding the complex stripping and transfer steps when using metal foil as a substrate.
[0015] The Cu 80 Ni 20 (111) The application of single-crystal thin films has solved the technical problems of traditional polycrystalline metal foils or single metal single-crystal substrates in terms of catalytic activity, lattice matching and large-scale preparation.
[0016] In the method of the present invention, the conditions for the thermal conversion treatment in step S1 are as follows: Introduce hydrogen gas at 120-140℃ for 10-15 minutes; The hydrogen flow rate is 300~500 sccm.
[0017] Due to the thermal instability of ammonia borane and the complexity of its decomposition products, it undergoes thermal conversion treatment.
[0018] Through the aforementioned thermal conversion treatment, the complex and unstable raw materials are transformed into a relatively homogeneous solid source that exists mainly in the form of borazine oligomers.
[0019] The heat-treated product decomposes more smoothly and uniformly at CVD growth temperatures, releasing borazine (B3N3H6) gas. The hydrogen atmosphere helps suppress oxidation and remove some volatile impurities, thereby reducing contamination sources during the growth process.
[0020] The thermal conversion treatment improves film uniformity: a stable and controllable borazine release rate ensures a stable precursor vapor concentration in the reaction chamber, providing crucial "gas source consistency" for the synchronous and uniform growth of multiple wafers.
[0021] The thermal conversion treatment improves crystal quality: Borazine is the ideal precursor molecule for growing h-BN, and its cyclic structure is highly similar to the six-membered ring structure of h-BN. Directly providing borazine molecular units reduces the complex assembly reaction steps on the metal substrate surface, making it easier to generate single-crystal h-BN with fewer defects and better crystallinity.
[0022] The thermal conversion treatment enhances process repeatability: by standardizing the pretreatment of the precursor, the differences between different batches and brands of ammonia borane raw materials are eliminated, which greatly improves the repeatability of each growth experiment, a prerequisite for achieving mass production.
[0023] The thermal conversion treatment can improve the utilization rate of precursors: the controlled release avoids the rapid depletion of precursors, making their utilization rate higher and the growth process more economical.
[0024] The thermal conversion process is not a simple preheating operation, but a step that actively regulates and optimizes the chemical properties of the precursor. It solves the problems of precursor instability and complex decomposition products in traditional methods from the source. Combined with the subsequent porous quartz sleeve (controlling the physical path of release) and stacked carrier (controlling the uniformity of the flow field), it forms a complete precision control system for the "generation-transport-growth" of the gas phase precursor, which ultimately ensures the high quality and high consistency of multiple wafers in a single batch.
[0025] In the method of the present invention, in step S2, the precursor vehicle includes: A precursor carrier body with a columnar structure, wherein a plurality of channels extending along its axial direction are provided on the precursor carrier body, and the channels are used to place the precursor receiving tube. The precursor receiving tube includes an outer sleeve with one end open and an inner sleeve with one end open, which is placed inside the outer sleeve. The open end of the inner sleeve is close to the closed end of the outer sleeve. The diameter of the channel is 10-15 mm.
[0026] The precursor vehicle possesses excellent heat resistance and gas diffusion control capabilities.
[0027] The precursor vehicle is made of quartz material, which has high temperature resistance, chemical inertness, and a low coefficient of thermal expansion. The double-layered sleeve design during the heating activation process effectively controls powder expansion and filters out particulate impurities generated during decomposition. The porous sleeve design allows the activated precursor to be uniformly diffused into the growth zone, providing a uniform flow field.
[0028] The application of the precursor vehicle in this invention solves many drawbacks of traditional evaporation boat vehicles, and its advantages are reflected in the following aspects: Controlling the precursor release rate. According to the principle of gas diffusion, the rate at which gas molecules escape through narrow channels is limited by the channel size. The smaller and more complex the channel, the greater the resistance to gas diffusion, and the slower and more stable the release rate. The quartz sleeve design of this invention avoids the excessively high local concentration caused by the instantaneous large-scale volatilization of the precursor in the initial stage of heating, as well as the sudden drop in concentration caused by rapid depletion in the later stage, thus transforming a violent and uncontrollable release process into a slow, stable, and sustainable release process.
[0029] Controlled release direction. The porous structure allows precursor vapor to diffuse evenly and diffusely from all directions of the sleeve wall, rather than being concentrated and ejected from a single large opening. Traditional open boats cause precursor vapor to concentrate and evaporate upwards, resulting in downstream wafers receiving more source gas and upstream wafers receiving less, causing batch inhomogeneity. The diffused release of the quartz sleeve facilitates faster and more uniform mixing in the gas flow, providing a gas source with a consistent concentration distribution in the reaction chamber.
[0030] Physical isolation and protection. The sleeve isolates the powdered precursor from the main gas flow channel. This prevents the gas flow from directly blowing on the powder, which could carry tiny powder particles to the growth area and cause defects on the wafer surface. The sleeve also ensures that the precursor is heated uniformly, preventing uneven decomposition caused by localized overheating or underheating.
[0031] In this invention, the precursor carrier, through the combination of thermal conversion treatment, stacked-layer wafer carrier, and CuNi single crystal substrate, achieves the following functions: Synergistic with thermal conversion treatment: The treated precursor becomes an oligomer that more easily and stably releases borazine, and the sleeve further ensures this stable release physically. The combination of these two methods completely solves the problem of unstable gas source from both chemical and physical perspectives.
[0032] In conjunction with stacked wafer carriers: the precursor carrier provides a uniform source, while the stacked carrier optimizes the airflow path from the source to each wafer. Together, they ensure a highly consistent gas phase environment for all wafers, which is an absolute prerequisite for achieving synchronous and uniform growth of more than 10 wafers in batches.
[0033] Synergistic effect with CuNi single crystal substrate: The stable and uniform gas source, combined with the lattice-matched and moderately catalytically active single crystal substrate, provides an ideal environment for the uniform nucleation and epitaxial growth of h-BN.
[0034] In the method of the present invention, in step S3, the wafer carrier includes a growth substrate tray, the growth substrate tray is provided with a plurality of wafer carrier components, and the wafer carrier components are provided with a plurality of wafer slots. Each layer of wafer slots on each group of wafer carrier assemblies is staggered from each layer of wafer slots on other groups of wafer carrier assemblies; The wafer carrier assembly includes at least three quartz pillars, and the wafer slots are evenly spaced along the axial direction of the quartz pillars.
[0035] The stacked wafer carrier optimizes the airflow channels and precursor transport paths, enabling simultaneous and uniform growth of multiple wafers while ensuring thermal uniformity.
[0036] The stacked wafer carrier presents a spiral upward three-dimensional structure by placing multiple wafers on steps of different heights. Each step carries one (or a few) wafers, and the wafer plane remains parallel to the airflow direction.
[0037] The wafer carrier plays the following roles by actively intervening in and optimizing the microenvironment within the reaction chamber: Achieving airflow homogenization (solving the gradient problem). In traditional parallel or stacked carriers, the airflow follows a "piston flow," where the preceding wafer consumes a large amount of reactant, leading to a significant decrease in gas phase concentration at the following wafers, creating a "shadowing effect" and causing a gradient distribution of film thickness and quality within a batch. The stepped structure breaks the direct linear airflow path. At each step, the airflow generates vortices and remixes. This process rehomogenizes the gas consumed by the upstream wafer with fresh gas before it contacts the next wafer. This ensures that the reactant concentration encountered by each wafer is essentially the same.
[0038] Ensuring thermal uniformity is crucial. Distributing wafers in a three-dimensional space avoids localized heat accumulation and mutual shading caused by dense stacking, ensuring that each wafer is uniformly heated by the reaction chamber's heating system and kept at nearly the same temperature. Temperature is one of the most critical parameters affecting reaction kinetics in CVD growth, and thermal uniformity is fundamental to achieving consistent growth.
[0039] Achieve true batch synchronous growth. The stacked structure allows for the accommodation of more than 10 wafers in a single growth run, ensuring they are in nearly identical chemical vapor and thermal environments.
[0040] Co-optimization with the flow field. For example... Figure 4 As shown in the simulation diagram, the design of the stacked wafer carrier matches the overall airflow pattern of the CVD system, guiding the airflow to flow through each wafer surface in the most efficient way, maximizing precursor utilization and growth uniformity.
[0041] In this invention, the stacked wafer carrier acts as a "bridge" connecting the "gas source" and the "substrate." Through its cooperation with the quartz sleeve and the CuNi single crystal substrate, it performs the following functions: In conjunction with the quartz sleeve: the quartz sleeve provides a stable, diffused air source, while the layered carrier creates a uniformly distributed airflow channel. The combination of the two ensures uniformity throughout the entire process from source to destination.
[0042] Synergistic with CuNi single-crystal thin films: It provides an equal and optimal growth environment for every expensive single-crystal substrate, allowing the excellent epitaxial potential of all substrates to be fully realized and avoiding quality differences caused by different locations.
[0043] This invention enables the simultaneous preparation of more than 10 uniform, high-quality single-crystal h-BN wafers in a single CVD growth reaction system, significantly improving production efficiency and possessing the potential for large-scale scaling.
[0044] In the method of the present invention, in step S3, the precursor carrier is placed upstream of the CVD reaction chamber, and the stacked wafer carrier is placed at the center of the CVD reaction chamber.
[0045] In the method of the present invention, the conditions for epitaxial growth in step S3 are as follows: After heating to the growth temperature at ambient pressure, switch to low pressure conditions of 50-100 Torr and grow for 30-60 minutes.
[0046] The epitaxial growth process is carried out in a CVD system and is a precisely controlled gas-phase-surface reaction process, allowing h-BN crystals to grow on Cu. 80 Ni 20 (111) Orderly growth on a single crystal substrate.
[0047] The volume ratio of hydrogen to argon is 1:3, and the flow rate is 1000 scmm:3000 sccm. Hydrogen can be used as: a reducing agent to prevent oxidation of the metal substrate surface, keeping it clean and highly catalytically active; an etchant to slightly etch away poor-quality or misoriented h-BN small crystal nuclei, promoting the formation of larger single crystal domains; and a carrier gas to transport precursor vapor to the growth region.
[0048] Argon is mainly used as a dilution gas and carrier gas to adjust the partial pressure and total pressure of the precursor and control the reaction rate.
[0049] The epitaxial growth includes an atmospheric pressure heating stage and a low pressure growth stage: Atmospheric pressure heating stage: Under atmospheric pressure (-760 Torr), the system is heated to 1050-1100°C at a rate of 15°C / min. The main purpose of this stage is to ensure that the substrate and carrier reach the growth temperature uniformly and stably, avoiding thermal stress; and to perform in-situ annealing of the substrate in a hydrogen atmosphere to further repair defects and obtain an atomically smooth and clean surface.
[0050] Low-pressure growth stage: After reaching the target temperature, the system pressure is reduced to 50-100 Torr (low-pressure environment). This stage is the core stage of h-BN epitaxial growth. Low pressure helps increase the mean free path of gas molecules, allowing precursor vapor to diffuse more effectively to each wafer layer of the substrate, improving uniformity; and it inhibits homogeneous nucleation in the gas phase (the precursor reacts spontaneously in the gas phase to form powder), forcing the reaction to mainly occur on the substrate surface, which is beneficial for generating clean, high-quality films.
[0051] In the method of this invention, the microscopic mechanism of epitaxial growth is as follows: Precursor transport and decomposition: Borazine (B3N3H6) vapor is smoothly released from the porous quartz sleeve, carried by the carrier gas, and flows through the stacked carrier. In the uniform flow field, each wafer comes into contact with a precursor of similar concentration.
[0052] Surface catalysis and decomposition: Borazine molecules diffuse to the high-temperature CuNi(111) substrate surface and are catalytically decomposed into active boron (B) and nitrogen (N) atom species.
[0053] Surface migration and nucleation: B and N atoms adsorb on the substrate surface and migrate at high speed. Due to the low mismatch between the CuNi(111) lattice and the h-BN lattice, atoms preferentially nucleate at specific sites (such as step edges) and begin to align along a relationship determined by the orientation of the substrate crystal.
[0054] Epitaxial growth and crystal zone merging: The crystal nucleus gradually grows into an h-BN single crystal island.
[0055] Since all crystal nuclei are guided by the lattice of the same single-crystal substrate, they have the same crystal orientation. These uniformly oriented crystal islands merge seamlessly during growth, forming a seamless (grain boundary-free) single-crystal thin film. Even if grain boundaries exist, they are "coherent grain boundaries" with extremely low energy, having minimal impact on electrical properties.
[0056] Termination of growth: After 30-60 minutes of growth, turn off the precursor heating source and stop heating. Allow the system to cool naturally to room temperature in an H2 / Ar atmosphere. The hydrogen environment protects the grown h-BN film and metal substrate from oxidation during cooling.
[0057] The single-crystal boron nitride wafer prepared by this invention has an ultra-smooth surface, high crystal quality, and excellent electrical insulation properties.
[0058] The single-crystal boron nitride wafer of this invention can be used in the following fields: 1) Two-dimensional material heterojunction devices; The single-crystal boron nitride wafer serves as a substrate, encapsulation layer, or tunneling insulating layer. 2) Deep ultraviolet optoelectronic devices; The single-crystal boron nitride wafer serves as a substrate or encapsulation layer. 3) Quantum device platform; The single-crystal boron nitride wafer serves as an insulating isolation layer or interface smoothing layer for the quantum bits. 4) Field-effect transistor; The single-crystal boron nitride wafer serves as a gate insulating layer or an interface modification layer. 5) Integrated circuit packaging; The single-crystal boron nitride wafer serves as a dielectric layer or thermal management layer. 6) Flexible electronic devices; The single-crystal boron nitride wafer serves as an insulating layer or encapsulation layer on a flexible substrate.
[0059] The present invention has the following beneficial technical effects: It has achieved the simultaneous batch production of high-quality single-crystal h-BN: for the first time, more than 10 wafers can be produced in a single growth in a single CVD system, breaking through the bottleneck of traditional methods that are limited to single-wafer or a few-wafer production. The production efficiency has been significantly improved, and it has the potential to move towards industrial-scale production.
[0060] A single-crystal thin film with excellent crystal quality and complete structure was obtained: the prepared h-BN wafer has a highly consistent crystal orientation and a seamless, grain boundary-free structure. Characterization by LEED and Raman spectroscopy confirmed that it is a high-quality single crystal. The surface is atomically smooth with a roughness of less than 0.5 nm, which greatly reduces interface scattering in two-dimensional devices and is beneficial to improving electron mobility and device performance.
[0061] Excellent batch uniformity and process repeatability were achieved: thanks to the multi-level control strategy of precursor pretreatment-porous sleeve-stacked carrier, the thickness, crystal quality and surface morphology of all wafers in the same batch showed high consistency, which solved the gradient effect and fluctuation problem in multi-wafer growth and ensured the predictability and high yield of manufacturing results.
[0062] Two major technical challenges—instable precursor decomposition and uneven gas flow distribution—were solved: Pre-conversion treatment of ammonia borane enabled stable and controllable release of borazine, preventing impurity introduction and uneven decomposition at the source. The stacked quartz carrier, through optimized flow field design, ensured a uniform distribution of thermal environment and gas phase concentration within the reaction chamber, placing each wafer under nearly identical growth conditions.
[0063] A solution compatible with existing semiconductor processes is provided: using c-plane sapphire as the substrate, single-crystal CuNi thin films are prepared by magnetron sputtering and high-temperature annealing. These processes are compatible with mainstream semiconductor manufacturing equipment, have controllable costs, and are easy to scale up. The grown h-BN / sapphire structure facilitates direct device fabrication or transfer, eliminating the complex etching and stripping steps required for traditional metal foil growth.
[0064] This broadens the application prospects of single-crystal h-BN in high-end devices: the prepared high-insulation, ultra-flat single-crystal h-BN wafers can be used as ideal substrates, gate dielectric layers or encapsulation layers, and have a wide range of applications.
[0065] This invention, through multi-dimensional synergy of material system innovation (CuNi single crystal substrate), precursor chemical regulation, reaction engineering design (sleeve and carrier), and growth process optimization, successfully solves the fundamental problem of the long-standing difficulty in balancing quality, uniformity, repeatability, and scalability in the preparation of single crystal h-BN, providing a reliable and efficient preparation path for the industrial application of two-dimensional insulating materials. Attached Figure Description
[0066] Figure 1 This is the design concept of the boron nitride batch preparation method of the present invention.
[0067] Figure 2 The images show the physical image and surface morphology of the copper-nickel single-crystal wafer prepared in Example 1 of this invention; wherein, image A is a physical image of the four-inch copper-nickel alloy single-crystal wafer, image B is an optical micrograph of the copper-nickel single-crystal wafer, and image C is an atomic force microscopy characterization image of the copper-nickel single-crystal wafer.
[0068] Figure 3 This is a three-dimensional schematic diagram of the precursor vehicle used in this invention.
[0069] Figure 4 This is a cross-sectional view of the precursor vehicle used in this invention.
[0070] Figure 5 This is a schematic diagram of the double-sleeve system in the precursor vehicle used in this invention.
[0071] Figure 6 This is a three-dimensional schematic diagram of the stacked wafer carrier used in this invention.
[0072] Figure 7 Figure A shows the simulated flow field distribution of gas mass transfer and flow field in the CVD system. Figure B shows the simulated flow field distribution of the precursor carrier and the simulated flow field distribution of the growth substrate carrier.
[0073] Figure 8 This is a process diagram for the batch fabrication of boron nitride wafers in Example 4 of the present invention.
[0074] Figure 9 The images shown are: physical image (A), surface AFM image (B), and LEED spectrum (C) of the h-BN wafer prepared in Example 4 of this invention.
[0075] Figure 10 The images show the Raman spectra (Figure A), white light interference morphology characterization (Figure B), and AFM characterization (Figure C) of 10 wafers prepared in the same batch in Example 4 of this invention.
[0076] Figure 11 The images show a comparison of scanning electron microscopy (SEM) images of boron nitride growth on copper foil and single-crystal CuNi(111) wafers. Image A is an SEM image of the boron nitride domain region on the copper foil, image B is an SEM image of the boron nitride thin film on the copper foil, image C is an SEM image of the boron nitride domain region on the single-crystal CuNi(111) wafer, and image D is an SEM image of the boron nitride thin film on the single-crystal CuNi(111) wafer.
[0077] Figure 12 The figures show the uniformity test results of the growth of a four-inch boron nitride wafer in Comparative Example 3. Figure A shows the growth results of the process of the present invention, and Figure B shows the growth results of the conventional process.
[0078] Figure 13 The following are the batch-to-batch yield stability statistics curves for Comparative Example 3 (data from 10 consecutive batches of production). Figure A shows the distribution of typical Raman peaks in the boron nitride thin films prepared in the 10 batches of samples, and Figure B shows the roughness statistics of boron nitride wafers in the 10 batches of samples.
[0079] Figure 14 SEM characterization of the entire growth process under normal pressure. Detailed Implementation
[0080] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0081] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0082] This invention provides a method for the batch preparation of single-crystal boron nitride (h-BN) wafers, belonging to the field of two-dimensional material preparation and nanoelectronic device manufacturing technology. It aims to solve the problems of inconsistent crystal orientation, poor surface flatness, low batch repeatability, and difficulty in large-scale production in existing single-crystal h-BN preparation technologies, ultimately achieving simultaneous epitaxial growth of multiple high-quality single-crystal h-BN wafers. The main steps include: 1. Preparation of single-crystal alloy growth substrate: A Cu layer with a thickness of 300-800 nm was deposited on a c-plane sapphire substrate by magnetron sputtering. 80 Ni 20 alloy film.
[0083] Under an H2 / Ar atmosphere, the alloy thin film is subjected to high-temperature annealing treatment at 1000-1100°C for 60-180 minutes to make it epitaxially recrystallized into a (111) oriented single crystal thin film with an atomically flat surface (roughness <0.5 nm), which serves as a template for the epitaxial growth of h-BN.
[0084] 2. Pretreatment and controlled supply of precursors: Using ammonia borane (NH3·BH3) as a precursor, it was thermally converted at -100°C in a hydrogen atmosphere to form an oligomer that mainly releases borazine (B3N3H6).
[0085] The processed precursor is placed in a specially designed porous precursor carrier. This carrier allows for the physical control of the release rate and direction of the gaseous precursor by adjusting the position and quantity of the precursor, ensuring the stability and uniformity of the gas source concentration within the reaction chamber.
[0086] 3. Constructing a reaction system with a uniform growth environment: A quartz-based stacked (stepped) wafer carrier is used to support multiple growth substrates. Through optimized interlayer height and horizontal offset design, this carrier ensures thorough remixing of gas flow at each wafer location, thereby guaranteeing that all wafers are in a nearly uniform gas concentration and thermal environment.
[0087] 4. Collaboratively optimized epitaxial growth process: The loaded system is placed in the CVD reaction chamber and heated to the growth temperature (1050-1100°C) under atmospheric pressure in an H2 / Ar mixed atmosphere to achieve thermal stability of the system.
[0088] The system was then switched to a low-pressure environment of 50-100 Torr for 30-60 minutes for epitaxial growth. The low-pressure environment effectively suppressed gas-phase nucleation and promoted the migration and ordered epitaxy of the precursor on the surface of the single-crystal CuNi(111) substrate, ultimately forming a high-quality single-crystal h-BN thin film.
[0089] This invention enables the simultaneous fabrication of more than 10 high-quality single-crystal h-BN wafers with consistent crystal orientation, smooth surfaces, and no grain boundaries in a single growth process. It boasts significant advantages such as high crystal quality, good uniformity, strong process repeatability, and scalability for large-scale production. The fabricated h-BN wafers have important application value in fields such as two-dimensional electronic devices, deep ultraviolet optoelectronics, quantum computing, and integrated circuit packaging.
[0090] Example 1: Preparation of the growth substrate A c-plane sapphire single crystal was selected as the substrate, and Cu was deposited on its surface using magnetron sputtering. 80 Ni 20 The alloy thin film has a thickness of approximately 500 nm. Subsequently, it was annealed at 1100°C for 180 minutes in an H2 / Ar atmosphere to drive the epitaxial rearrangement of the Cu-Ni thin film on sapphire to form a (111) oriented single-crystal Cu-Ni thin film, thereby obtaining a high-quality growth substrate with a surface roughness of less than 0.5 nm.
[0091] The physical image and surface morphology image of the copper-nickel single crystal wafer prepared in this embodiment are shown below. Figure 2 As shown, Figure 2 Image A shows a physical image of a four-inch copper-nickel alloy single-crystal wafer. Figure 2 Image B in the middle is an optical micrograph of a copper-nickel single-crystal wafer, showing the absence of twin boundaries. Figure 2 Figure C shows an atomic force microscopy characterization of a copper-nickel single-crystal wafer, which has an ultra-smooth surface with a roughness of only 0.410 nm.
[0092] Example 2: Porous precursor vehicle The porous precursor vehicle structure used in this invention is as follows: Figures 3-5 As shown, where, Figure 3 A three-dimensional schematic diagram of the precursor vehicle. Figure 4 This is a cross-sectional view of the precursor vehicle. Figure 5 This is a schematic diagram of a double-sleeve system in a precursor vehicle.
[0093] The precursor carrier provided by this invention includes a precursor carrier body 1 with a columnar structure. The precursor carrier body 1 has several channels 2 (with a diameter of 10-15 mm) extending axially along its axis. The channels 2 are used to place a precursor receiving tube 3. The precursor receiving tube 3 includes an outer sleeve 5 open at one end and an inner sleeve 4 open at one end, placed inside the outer sleeve 5. The open end of the inner sleeve 4 is close to the closed end of the outer sleeve 5. The precursor ammonia borane powder is placed in the inner sleeve 4. The double-layer sleeve design during the heating activation process can effectively control the expansion of the powder and filter out particulate impurities generated during decomposition. The porous sleeve design allows the activated precursor to be uniformly diffused into the growth zone, providing a uniform flow field.
[0094] Specifically, in the double-sleeved precursor carrier of the present invention, the openings of the inner sleeve 4 and the outer sleeve 5 are designed with opposite orientations. The opening of the inner sleeve 4 faces downwards ( Figure 5 For illustrative purposes only. In actual production, the precursor container tube 3 is placed vertically, with the inner sleeve 4 opening downwards and the outer sleeve 5 opening upwards. This creates a localized high-pressure environment inside the tube during the reaction. Utilizing the pressure sensitivity of the ammonia borane decomposition reaction, the decomposition rate is actively suppressed from a chemical kinetic perspective, thus preventing violent expansion and splashing of the powder from the source. The outer sleeve 5, with its upward opening, serves as the sole outlet for the pure precursor, ensuring that the airflow direction is consistent with the thermal convection direction, efficiently transporting the precursor to the growth region.
[0095] The design of this double-layer casing integrates the functions of precursor activation, expansion suppression, impurity filtration, and uniform transport through a synergistic mechanism of "inner layer pressure control to suppress decomposition and outer layer flow guidance to optimize transport". This achieves unprecedented precision control over the decomposition process of ammonia borane and lays the core equipment foundation for high-quality, mass production of single-crystal boron nitride.
[0096] Example 3: Wafer carrier The wafer carrier structure used in this invention is as follows: Figure 6 As shown, the device includes a growth substrate tray 6, on which several sets of wafer carrier assemblies are disposed, and several layers of wafer slots 8 are disposed on the wafer carrier assemblies. Preferably, each layer of wafer slots 8 on each set of wafer carrier assemblies is staggered from each layer of wafer slots 8 on other sets of wafer carrier assemblies. Specifically, the wafer carrier assembly includes at least three quartz pillars 7, and the wafer slots 8 are uniformly spaced along the axial direction of the quartz pillars 7.
[0097] like Figure 6 As shown, in a preferred embodiment of the present invention, the growth substrate carrier can hold 10 copper-nickel wafers at a time for boron nitride growth. The quartz pillars 7 can embed the thin wafers into the wafer slots 8, and the designed staggered slot structure can achieve uniform airflow coverage, ensuring the uniformity of multi-wafer growth.
[0098] To further optimize the flow field distribution within the reaction chamber, this invention also designs a growth substrate carrier with a staggered structure to support the wafer substrate. This staggered structure can guide the airflow, which has been initially homogenized by the porous sleeve, to flow smoothly and laminarly across each wafer surface, avoiding the generation of eddies and local turbulence, and ensuring that the mass transport rate of the precursor gas is consistent across each wafer surface.
[0099] Computational fluid dynamics simulations have verified that the uniformity of the flow field distribution within the reaction chamber is significantly improved after adopting the carrier structure of this invention (see simulation results). Figure 7 After the airflow passes through the precursor carrier, the flow field is uniformly distributed. The uniform flow field distribution enables the precursor to be delivered to all substrate surfaces simultaneously and in equal quantities, thereby achieving synchronous and uniform epitaxial growth of more than ten four-inch boron nitride wafers at one time.
[0100] Example 4: Preparation of h-BN single crystal thin films 1. Precursor regulation Ammonia borane (NH3·BH3) was used as a precursor. To improve its decomposition efficiency and stability, it was subjected to thermal conversion treatment at 100°C while hydrogen gas was introduced at 500 sccm to preferentially generate a reaction precursor mainly composed of borazine (B3N3H6).
[0101] The processed precursor is encapsulated in a quartz inner sleeve 4. Since the opening direction of the inner sleeve 4 is opposite to that of the outer sleeve 5, the airflow enters from the opening of the outer sleeve 5. Then, the precursor receiving tube 3 is placed in the channel 2 on the precursor carrier body 1. By adjusting the gap width between the two sleeves, combined with the number and position of the precursor placed in the porous sleeve, the release rate and concentration of the gaseous substance can be controlled to ensure uniform distribution of the source substance in the reaction chamber.
[0102] 2. Airflow control Each carrier can accommodate 10 Cu-Ni wafers, with the interlayer height and gas flow diffusion length optimized to ensure that all wafers are in approximately the same gas phase concentration and thermal environment. This structure exhibits good thermal stability and chemical inertness, and can be used for extended periods at temperatures above 1100°C.
[0103] 3. Epitaxial growth of h-BN single crystal thin films The quartz stacked carrier with the loaded substrate is placed in the central region of the CVD reaction chamber, and the sleeve precursor source is placed upstream of the heating zone.
[0104] like Figure 7The diagram shows a simulation of gas mass transfer and flow field in a CVD system. It can be seen that when the precursor carrier gas carrying the source material flows through the casing, the concentrated gas flow is forcibly dispersed and released diffusely through the porous structure of the precursor carrier. This design transforms the traditional point-jet source into a large-surface-area, uniformly distributed planar diffusion source, thereby forming a uniform and stable precursor concentration field within the reaction chamber.
[0105] Growth conditions such as Figure 8 As shown, the system was purged with a hydrogen / argon mixed atmosphere (H2:Ar=1:3), and the pressure was controlled at atmospheric pressure. The temperature was increased to the boron nitride growth temperature at a rate of 15°C per minute, and then switched to low-pressure growth conditions, with the pressure controlled at 50 Torr. The reaction growth was carried out at 1050°C for 30 minutes. h-BN was epitaxially grown along a preferred direction on a CuNi(111) substrate to form a single crystal film with high crystallinity and high flatness.
[0106] like Figure 9 As shown, the AFM image and LEED spectrum of the h-BN wafer surface prepared in this embodiment can be seen. It can be seen that the obtained h-BN thin film has an ultra-flat surface and a long-range ordered single crystal structure.
[0107] Specifically, the AFM images showed that the surface roughness value was less than 0.5 nm, and no obvious wrinkles, cracks or polymer residues were observed throughout the entire scanning area (e.g., 20 nm), confirming that the film has atomic-level flatness, which meets the flatness requirements of the interface encapsulation layer for high-end electronic devices.
[0108] Meanwhile, the LEED pattern exhibits clear, sharp diffraction spots with six-fold symmetry, regular spot shapes, and extremely low background noise. This diffraction pattern indicates that the grown h-BN film is a single-crystal structure with highly consistent lattice orientation, further confirming the excellent crystal quality and long-range order of the prepared h-BN wafer.
[0109] like Figure 10The figures show Raman spectra, white light interference morphology characterization images, and AFM characterization images of 10 wafers prepared in the same batch in this embodiment. It can be seen that the obtained h-BN thin film possesses an ultra-smooth surface and a long-range ordered single-crystal structure. Nine regions of the prepared ultra-smooth single-crystal boron nitride wafer were selected for AFM and LEED characterization. The AFM images show a surface roughness value of less than 0.5 nm, and no obvious wrinkles, cracks, or polymer residues were observed in the entire scanning area (10 μm × 10 μm), confirming that the film has atomic-level flatness, meeting the flatness requirements of the interface encapsulation layer for high-end electronic devices. Simultaneously, the LEED spectrum exhibits clear, sharp diffraction spots with six-fold symmetry, regular spot shapes, and extremely low background noise. This diffraction pattern indicates that the grown h-BN thin film has a single-crystal structure with highly consistent lattice orientation, further confirming from an electronic structure perspective that the prepared h-BN wafer has excellent crystal quality and long-range order.
[0110] In summary, the present invention provides a method for the simultaneous batch production of high-quality single-crystal boron nitride wafers based on a copper-nickel single-crystal thin film substrate and a gas source / flow field precision control strategy. This method enables the simultaneous production of more than 10 uniform, high-quality single-crystal h-BN wafers in a single CVD growth reaction system, significantly improving production efficiency and possessing the potential for large-scale scaling.
[0111] Comparative Example 1: Using traditional polycrystalline copper foil as the growth substrate Except for the growth substrate, the other conditions were exactly the same as in Example 4.
[0112] Commercial polycrystalline copper foil (25 μm thick) was used instead of Cu in this invention. 80 Ni 20 (111) / Sapphire single crystal substrate.
[0113] The precursor also undergoes thermal conversion treatment and is grown using a porous quartz sleeve and a stacked carrier.
[0114] Result: As Figure 11 As shown in Figures A and B, h-BN grown on copper foil was characterized by scanning electron microscopy (SEM) of the boron nitride domain regions and thin films grown on the copper foil. The boron nitride domain regions grown on the copper foil exhibit random orientation, resulting in numerous grain boundaries and wrinkles after complete coverage, making it impossible to obtain single-crystal boron nitride thin films. Figure 11 Figures C and D show the use of Cu in this invention. 80 Ni 20 (111) / Boron nitride grown on a sapphire single crystal substrate can be seen to have regular triangular domain regions with almost identical orientation. After complete coverage, scanning electron microscopy characterization shows that its surface is flat, without wrinkles or grain boundaries. The boron nitride thin film prepared by this invention has a flat surface and good single crystal properties.
[0115] This comparative example demonstrates that a single-crystal CuNi(111) substrate is indispensable for obtaining high-quality single-crystal h-BN with consistent crystal orientation and no grain boundaries, while the multiple crystal orientations on the surface of a polycrystalline substrate cannot guide the epitaxial growth of single-crystal boron nitride films.
[0116] Comparative Example 2: Using untreated ammoniaborane directly as a precursor Except for the precursor, the other conditions were exactly the same as in Example 4.
[0117] Commercial ammonia borane powder was used directly without thermal conversion treatment with H2 at 130°C.
[0118] It was loaded into a porous precursor carrier and grown on a CuNi(111) / sapphire substrate using a stacked-layer carrier.
[0119] Results: The nucleation density of the h-BN film was non-uniform, containing many nitrogen-rich or boron-rich impurity phases (XPS detection). The characteristic peak of h-BN in the Raman spectrum (1366 cm⁻¹) was observed. -1 An increase in the full width at half maximum (FWHM) and a shift in peak position indicate a decrease in crystal quality and uneven stress. This leads to a decrease in the insulation performance of the thin film and an increase in leakage current.
[0120] This comparative example demonstrates that precursor thermal conversion treatment is crucial for obtaining a pure and stable borazine gas source, and is a key chemical control step to ensure high crystallinity and batch repeatability of h-BN.
[0121] Comparative Example 3: Using a traditional CVD tube furnace Figure 12 The results of growth using the apparatus of this invention (precursor carrier and stacked carrier) compared to conventional CVD tube furnace are demonstrated.
[0122] Traditional CVD tube furnaces cannot achieve wafer coverage for boron nitride; after baking on a hot stage, the uncovered areas are oxidized. Wafers grown using the batch fabrication apparatus of this invention can achieve uniform, full-coverage growth. The uniformity and roughness of boron nitride wafers grown in 10 batches were statistically analyzed using Raman spectroscopy and atomic force microscopy. Figure 8 As shown. Figure 13 Figure A shows that the characteristic spectral peak E2g of 10 batches of boron nitride wafers prepared by the apparatus of this invention is located near 1367 cm⁻¹ and is uniformly distributed within a range of hundreds of micrometers. Atomic force microscopy analysis of the roughness of the 10 batches of boron nitride wafers showed that all were below 0.5 nm, exhibiting ultra-smooth characteristics.
[0123] This comparative example demonstrates that the synergistic design of porous precursor carriers (controlled release) and stacked carriers (homogenized flow field) is the core technical feature for solving gradient problems and achieving high uniformity in multi-piece batch growth.
[0124] Comparative Example 4: Complete growth under normal pressure Except for growth pressure, the other conditions are exactly the same as those of the present invention.
[0125] From the start of heating to the end of growth, the entire process was kept at atmospheric pressure (-760 Torr), without employing the atmospheric pressure heating + low pressure growth strategy of this invention.
[0126] like Figure 14 Results shown: Nucleation was intensified in the gas phase, and a large amount of white BN powder was deposited in the reaction chamber, contaminating the furnace tube and sample surface. The surface of the grown h-BN film showed increased adsorbates, and AFM revealed an increased defect density. The excessively high nucleation density of the film resulted in smaller crystal domains, leading to more defects after merging.
[0127] This comparative example demonstrates that the low-pressure growth stage plays a crucial role in suppressing gas-phase side reactions, reducing nucleation density, promoting surface migration, and achieving high-quality epitaxial growth.
Claims
1. A method for batch production of single-crystal boron nitride wafers, comprising the following steps: S1. subjecting an ammonia borane precursor to thermal conversion treatment to form a stable borazine gas-phase precursor release source system; S2. placing the precursor treated in step S1 into a precursor containing tube in a precursor carrier with a porous structure, for regulating the release rate and direction of the gas-phase precursor; S3. placing a growth substrate into a wafer carrier, and placing it into a CVD reaction chamber, and introducing a mixture of hydrogen and argon gas, and performing epitaxial growth at 1050-1100 °C to achieve simultaneous production of multiple single-crystal boron nitride wafers.
2. The method of claim 1, wherein: The growth substrate is Cu 80 Ni 20 (111) single crystal thin film; The Cu 80 Ni 20 The surface roughness of the (111) single crystal thin film is less than 0.5 nm.
3. The method of claim 2, wherein: The Cu 80 Ni 20 A (111) single crystal thin film is prepared according to a method comprising the steps of: A copper-nickel alloy thin film is deposited by magnetron sputtering on a c-plane sapphire substrate and annealed in a hydrogen and argon mixed atmosphere at 1000-1100°C for 60-180 minutes to form a Cu 80 Ni 20 (111) oriented monocrystalline thin film substrate.
4. The batch production method according to any one of claims 1 to 3, characterized in that: In step S1, the thermal conversion treatment is performed under the following conditions: introducing hydrogen gas at 120-140 °C for 10-15 minutes.
5. The batch production method according to any one of claims 1 to 3, characterized in that: In step S2, the precursor carrier comprises: a precursor carrier body with a columnar structure, and a plurality of channels extending along the axial direction of the precursor carrier body, the channels being used for placing the precursor containing tube; the precursor containing tube comprises an outer sleeve with an open end, and an inner sleeve with an open end placed in the outer sleeve, and the open end of the inner sleeve is close to the closed end of the outer sleeve.
6. The batch production method according to any one of claims 1 to 3, characterized in that: In step S3, the wafer carrier comprises a growth substrate tray, and a plurality of sets of wafer carrying assemblies are arranged on the growth substrate tray, and a plurality of layers of wafer clamping grooves are arranged on the wafer carrying assemblies; each layer of wafer clamping grooves on each set of wafer carrying assemblies is arranged in a staggered manner with each layer of wafer clamping grooves on other sets of wafer carrying assemblies.
7. The batch production method according to any one of claims 1 to 3, characterized in that: In step S3, the precursor carrier is placed upstream of the CVD reaction chamber, and the wafer carrier is placed in the center of the CVD reaction chamber.
8. The batch production method according to any one of claims 1 to 3, characterized in that: In step S3, the epitaxial growth is performed under the following conditions: after the temperature is raised to the growth temperature under normal pressure, the pressure is switched to a low pressure of 50-100 Torr, and the growth time is 30-60 minutes.
9. A single-crystal boron nitride wafer produced by the method of any one of claims 1-8; the single-crystal boron nitride wafer has an ultra-flat surface, high crystalline quality, and excellent electrical insulation performance.
10. Use of the single-crystal boron nitride wafer of claim 9 in: 1) preparation of two-dimensional material heterojunction devices; the single-crystal boron nitride wafer as a substrate, encapsulation layer, or tunneling insulation layer; 2) deep ultraviolet optoelectronic devices; the single-crystal boron nitride wafer as a substrate or encapsulation layer; 3) quantum device platforms; the single-crystal boron nitride wafer as an insulating isolation or interface flattening layer for quantum bits; 4) field effect transistors; the single-crystal boron nitride wafer as a gate insulating layer or interface modification layer; 5) integrated circuit packaging; the single-crystal boron nitride wafer as a dielectric layer or thermal management layer; 6) flexible electronic devices; the single-crystal boron nitride wafer as an insulating layer or encapsulation layer on a flexible substrate.
Citation Information
Patent Citations
Growth method and device of graphene wafer
CN114657531A
Method for preparing four-inch ultra-flat monocrystal hexagonal boron nitride wafer
CN118745594A
Two-dimensional material gas phase preparation equipment
CN215887222U
Preparing method of multi-layer hexagonal boron nitride nanostructure on sapphire substrate
KR1020170088037A
Cited By
Graphene / hexagonal boron nitride vertical heterojunction and preparation method thereof
CN121802543A